Evaluation of relative distribution and risk factors in patients with dry socket referring to Yazd dental clinics - Hasan Momeni; Shirin Shahnaseri; Zeinab Hamzeheil (Wolters Kluwer Medknow Publications, 2011)
Background: Dry socket is one of the most prevalent complications occurring after tooth extraction. The prevalence of such condition has been reported to be highly different, ranging from 0.5 to 68.4%. The etiology and pathogenesis of this entity are not clearly known and many related predisposing factors have been discussed. The goal of this study was to evaluate the relative prevalence of this entity after tooth extraction and determine the contributing factors in patient referring to Yazd dental clinics. Materials and Methods: This cross-sectional prospective study was carried out at Yazd dental clinics (from May 2010 to Jun 2010). Four thousand seven hundred and seventy nine patients were selected and included in our study. Characteristics such as: age, gender, site of extraction, number of extracted tooth, trauma during extraction, oral hygiene, smoking, systemic disease, menstrual cycle, history of dental infection and oral contraceptive pill intake were determined and data was analyzed using descriptive statistical analysis and Fisher's exact test. P value ≤0.05 was considered significant. Results: Over the two-month period of the study, among of 4,779 patients, 28 patients returned with dry socket phenomena. Our results showed that the incidence of dry socket was 0.6% and females were more common involved than males (0.08% versus 0.04%). The ratio of mandible to maxilla was 2.5 to1 and mandibular third molars were more often involved than other teeth. Trauma, poor oral hygiene and smoking had increased the incidence of dry socket. Conclusion: The results of our study suggested that trauma during surgery or extraction and poor oral hygiene are important factors that increase the incidence of dry socket, these factors should be considered before and after tooth extractions.